Impacts of low-cost airlines on customer satisfaction of traditional airlines - Nascimento, Amanda Cristina (2019)
Project Work report presented as a partial requirement for obtaining the Master’s degree in Statistics and Information Management, with a specialization in Marketing Research e CRM